Redox interactions of nitric oxide with dopamine and its derivatives - Antunes, Fernando (2005)
Nitric oxide (NO) is a ubiquitous diffusible messenger in the central nervous system. NO and derived nitrogen species may interact with catecholamines, thus, modifying not only its regulatory actions but also producing oxidants and free radicals that are likely to trigger toxic pathways in the nervous system. Oxidative pathways and chain oxidation reactions triggered by catecholamines may be broken by ascorbate and glutathione, of which there is ample supply in the brain. At the subcellular level, mitochondria and cytosolic dopamine storage vesicles are likely to provide site-specific settings for NO and catecholamines interactions. Thus, a complex picture emerges in which the steady- state levels of the individual reactants, the rate constants of the reactions involved, the oxygen tension, and the compartmentalization of reactions determine the biological significance of the redox interactions between NO and dopamine metabolism in the brain. The physiological relevance of NO-driven chemical modifications of dopamine and its derivatives and the ensuing free radical production are discussed in connection with the neurodegeneration inherent in Parkinson's disease.